Dispersion, method for manufacturing dispersion, and molded article
Patent Information
- Application Number
- KR1020227013463
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-15
- Filing Date
- 2020-12-03
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2040-12-03
Smart Images

Figure 112022043045330-PCT00001 
Figure 112022043045330-PCT00002
Abstract
Description
Technology Field
[0001] The present invention relates to a dispersion containing a predetermined anisotropic filler, a method for manufacturing the same, and a molded article. Background Technology
[0002] Thermomeltable fluoropolymers, such as tetrafluoroethylene-based polymers (PFA) containing units based on perfluoro(alkyl vinyl ether) and tetrafluoroethylene-based polymers (FEP) containing units based on hexafluoropropylene, have excellent physical properties such as mold release, electrical insulation, water and oil repellency, chemical resistance, weather resistance, and heat resistance, and are processed into various molded articles and used.
[0003] Patent Document 1 describes a wire tube with excellent electrical insulation properties obtained by melt-kneading a dry blend of PFA powder and boron nitride filler and extruding it. Prior art literature
[0004] Japanese Published Patent Application No. 2014-224228 The problem to be solved
[0005] However, the melt viscosity of such fluoropolymers is generally high, so strong stress is required when melt-kneading the fluoropolymer and the filler. At that time, the original properties of the filler (especially physical properties such as shape and surface condition) are damaged, and the physical properties of the filler in the molded article are prone to deterioration. The inventors have discovered that this tendency is pronounced in the case of soft fillers with low hardness, and in particular, in the case of fillers that are also low hardness and anisotropic.
[0006] The inventors have carefully investigated to obtain a material suitable for molding such a molded article without melt mixing. As a result, it was discovered that a dispersion containing a powder of a predetermined fluoropolymer and a predetermined anisotropic filler has excellent dispersion stability and excellent handling properties such as coating properties. Furthermore, it was discovered that the molded article formed therefrom is unlikely to damage the original properties of the anisotropic filler and possesses the physical properties of both to a high degree.
[0007] The object of the present invention is to provide such dispersion and molded article. means of solving the problem
[0008] The present invention has the following aspects.
[0009] [1] A dispersion comprising a powder of a tetrafluoroethylene-based polymer containing a unit based on perfluoro(alkyl vinyl ether) or a unit based on hexafluoropropylene, an anisotropic filler having a Mohs hardness of 4 or less, and a liquid dispersion medium, wherein the average particle size of the powder is smaller than the average particle size of the anisotropic filler.
[0010] [2] A dispersion of [1] in which the content of the tetrafluoroethylene-based polymer and the content of the anisotropic filler are each 5 mass% or more.
[0011] [3] A dispersion of [1] or [2] in which the shape of the above anisotropic filler is flaky or plate-like.
[0012] [4] A dispersion of any of [1] to [3] in which the aspect ratio of the above anisotropic filler is 2 or more.
[0013] [5] A dispersion of any of [1] to [4], wherein the anisotropic filler is an anisotropic filler comprising boron nitride or talc.
[0014] [6] Additionally, a dispersion of any of [1] to [5] comprising a powder of polytetrafluoroethylene or an aromatic polymer.
[0015] [7] A dispersion of any of [1] to [6] in which the dispersion ratio of the components is 60% or more.
[0016] [8] A method for preparing a dispersion of any of [1] to [7], wherein the powder, the anisotropic filler, an inorganic filler having an average particle size smaller than that of the anisotropic filler, and a liquid dispersion medium are mixed.
[0017] [9] A method of manufacturing [8] by mixing, by stirring.
[0018]
[10] A molded article comprising a tetrafluoroethylene-based polymer containing a perfluoro(alkyl vinyl ether)-based unit and an anisotropic filler having a Mohs hardness of 4 or less,
[0019] A molded article wherein the tetrafluoroethylene-based polymer is a polymer having polar functional groups, or a polymer that does not have polar functional groups and contains 2.0 to 5.0 mol% of a unit based on the perfluoro(alkyl vinyl ether) with respect to the total unit, and the proportion of the anisotropic filler in the molded article is 10 mass% or more.
[0020]
[11] A molded product of which the aspect ratio of the above anisotropic filler is 2 or greater,
[10] .
[0021]
[12] A molded article of which the anisotropic filler is a scaly anisotropic filler containing boron nitride or a plate-like anisotropic filler containing talc.
[11]
[0022]
[13] A molded article of any of
[10] to
[12] having an average particle size of the above anisotropic filler of 1 μm or more.
[0023]
[14] Additionally, a molded article of any of
[10] to
[13] comprising polytetrafluoroethylene or an aromatic polymer.
[0024]
[15] The above molded article is a layered molded article with a thickness of 150 μm or less,
[10] to
[14] molded article. Effects of the invention
[0025] According to the present invention, a dispersion with excellent dispersibility and handling properties is obtained by including a powder of a predetermined fluoropolymer and a predetermined anisotropic filler. In addition, a molded article is obtained that highly possesses the physical properties of both and has particularly excellent electrical properties. Specific details for implementing the invention
[0026] The following terms have the following meanings.
[0027] "Average particle size (D50)" is the cumulative 50% diameter based on the volume of the object (powder or filler) obtained by the laser diffraction and scattering method. That is, the particle size distribution of the object is measured by the laser diffraction and scattering method, and a cumulative curve is obtained by setting the total volume of the particle group of the object to 100%, and it is the particle size at the point where the cumulative volume becomes 50% on the cumulative curve.
[0028] "D90" is the cumulative diameter of the object based on its volume, measured in the same way.
[0029] "Particle size distribution" is a distribution represented by a curve plotting the particle amount (%) in each particle size range obtained in the same way.
[0030] "Melting temperature" is the temperature corresponding to the maximum value of the polymer melting peak measured by differential scanning calorimetry (DSC).
[0031] The "glass transition point" is a value measured by analyzing the polymer using the Dynamic Viscoelastic Measurement (DMA) method.
[0032] In a polymer, a “unit” may be an atomic group formed directly from a monomer by a polymerization reaction, or an atomic group in which a part of the structure is transformed by treating the polymer obtained by the polymerization reaction by a predetermined method. A unit based on monomer A included in the polymer is also simply referred to as a “monomer A unit.”
[0033] The dispersion of the present invention (hereinafter also referred to as “the dispersion”) comprises a powder (hereinafter also referred to as “F powder”) of a tetrafluoroethylene-based polymer (hereinafter also referred to as “F polymer”) containing a unit based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE unit) or a unit based on hexafluoropropylene (HFP) (HFP unit), an anisotropic filler having a Mohs hardness of 4 or less, and a liquid dispersion medium.
[0034] In addition, the average particle size of the F powder is smaller than the average particle size of the anisotropic filler. In this dispersion, the F powder and the anisotropic filler are dispersed.
[0035] This dispersion exhibits excellent dispersion stability and handling properties, making it easy to form molded articles that possess highly effective physical properties of the F polymer and anisotropic filler. Although the reason for this is not necessarily clear, it can be considered as follows.
[0036] The anisotropic filler in the present invention may also be described as a brittle filler having an irregular shape and various characteristics (such as a static wall). In the dispersion, the anisotropic filler is unstable and prone to aggregation or sedimentation. Furthermore, the anisotropic filler is in a state where its shape or characteristics are prone to being destroyed by physical stress (such as shear stress).
[0037] Meanwhile, the F polymer is a polymer that has plasticity, characterized by its heat melt processability, and its powder (F powder) is resistant to physical stress and has excellent dispersibility.
[0038] The dispersion contains these F powders in a state smaller than the average particle size of the anisotropic filler—in other words, densely—so that the affinity between the anisotropic filler and the F powder is relatively high. In short, since the F powder is contained more finely and densely in the dispersion, it is thought that similar secondary particles are easily formed between the F powder and the anisotropic filler. As a result, the dispersion state of the anisotropic filler is stabilized, so the dispersion is thought to have excellent dispersion stability and handling properties.
[0039] Furthermore, when F powder is melt-fired from this dispersion while removing the liquid dispersion medium, it is easy to form a molded article while suppressing deformation of the anisotropic filler. Additionally, during the process of removing the liquid dispersion medium, the anisotropic filler is oriented, making it easy to obtain a highly filled molded article. As a result, it is believed that a molded article highly possessing the properties of the F polymer and the anisotropic filler is obtained from this dispersion.
[0040] For example, when a molded article is formed from the present dispersion containing flaky or plate-shaped anisotropic fillers, the anisotropic fillers are oriented parallel to the surface (plane direction) of the molded article, making it easy to highly express the physical properties of the anisotropic fillers in the molded article. Therefore, by using the present dispersion, it is easy to highly express the physical properties of the F polymer and the anisotropic fillers even in thin-layer molded articles.
[0041] Furthermore, if the anisotropic filler is in the form of flakes or plates, it forms a card house structure, which not only improves the liquid properties (viscosity, dispersion stability, etc.) of the dispersion but also facilitates higher dispersion of the anisotropic filler in the molded product formed therefrom. As a result, the molded product is likely to have excellent electrical properties. Additionally, when the molded product is subjected to stress, the stress is easily dispersed by the anisotropic filler, making it easy to improve mechanical strength (flexibility, etc.). Moreover, since a path of the anisotropic filler is formed in the molded product, the thermal conductivity of the molded product is likely to be improved.
[0042] In the dispersion, the F powder is preferably composed of an F polymer. The content of the F polymer in the powder is preferably 80 mass% or more, and more preferably 100 mass%.
[0043] Other components that may be included in the F powder include resins or inorganic materials different from the F polymer. Examples of different resins include aromatic polyesters, polyamideimides, thermoplastic polyimides, polyphenylene ethers, and polyphenylene oxides.
[0044] Examples of inorganic materials include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride, and magnesium metasilicate (steatite).
[0045] F powder containing a resin or inorganic material different from the F polymer preferably has a core-shell structure in which the F polymer is the core and the resin or inorganic material is the shell, or has a core-shell structure in which the resin or inorganic material is the core and the F polymer is the shell. Such F powder is obtained, for example, by bonding (collision, aggregation, etc.) the powder of the F polymer and the powder of the resin or inorganic material.
[0046] The D50 of the F powder is preferably 10 μm or less, more preferably 6 μm or less, and even more preferably 4 μm or less. The D50 of the F powder is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 1 μm or more. In addition, the D90 of the F powder is preferably 20 μm or less, and more preferably 10 μm or less. When the D50 and D90 of the F powder are within these ranges, the affinity with the anisotropic filler is further improved, making it easier to further improve the dispersion stability of the dispersion and the physical properties of the molded article.
[0047] The content of F powder in the dispersion is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 25 mass% or more. The content of F powder is preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 30 mass% or less. When the content of F powder is within these ranges, the affinity between the F powder and the anisotropic filler is increased due to the densely included F powder, making it easier to further improve the dispersion stability of the dispersion. In addition, the physical properties of the F polymer in the molded article are more likely to be significantly expressed.
[0048] The F polymer in the dispersion is a polymer containing a unit based on tetrafluoroethylene (TFE) (TFE unit). The F polymer may contain both PAVE units and HFP units, or only one of them.
[0049] PAVE is preferably CF2= CFOCF3, CF2= CFOCF2CF3, or CF2= CFOCF2CF2CF3(PPVE), and PPVE is more preferable.
[0050] The melting temperature of the F polymer is preferably 280 to 325 ℃, and more preferably 285 to 320 ℃.
[0051] The glass transition point of the F polymer is preferably 75 to 125 ℃, and more preferably 80 to 100 ℃.
[0052] The F polymer may have polar functional groups (oxygen-containing polar groups). The polar functional groups may be included in the units of the F polymer or in the terminal groups of the main chain of the polymer. Examples of the latter embodiment include an F polymer having polar functional groups as terminal groups derived from polymerization initiators, chain transfer agents, etc., and an F polymer having polar functional groups obtained by plasma treatment or ionization treatment of the F polymer.
[0053] The polar functional group is preferably a hydroxyl group or a carbonyl group, and from the perspective of dispersion stability of the dispersion, a carbonyl group is more preferable.
[0054] The hydroxyl group containing the group is preferably a group containing an alcoholic hydroxyl group, and -CF2CH2OH or -C(CF3)2OH is more preferable.
[0055] The carbonyl group containing the carbonyl group is a group containing a carbonyl group (> C(O)), and preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), or a carbonate group (-OC(O)O-).
[0056] The number of carbonyl groups in the F polymer is 1 × 10, the number of carbon atoms in the main chain. 6 For each, 10 to 5000 are preferred, 100 to 3000 are more preferred, and 800 to 1500 are even more preferred. In addition, the number of carbonyl group-containing groups in the F polymer can be quantified by the composition of the polymer or by the method described in International Publication No. 2020 / 145133.
[0057] As for the F polymer, a tetrafluoroethylene-based polymer containing PAVE units and containing 1.5 to 5.0 mol% of PAVE units relative to the total units is preferred, and a polymer (1) containing a unit based on a monomer having PAVE units and polar functional groups and having polar functional groups, or a polymer (2) not having polar functional groups containing PAVE units and containing 2.0 to 5.0 mol% of PAVE units relative to the total units is more preferred.
[0058] These F polymers not only have excellent dispersion stability as powders, but also tend to be distributed more densely and homogeneously within the molded article (polymer layer, etc.) formed from the dispersion. Furthermore, they tend to form microspheres within the molded article, which facilitates high adhesion to other components. As a result, it is easier to obtain a molded article that possesses highly developed physical properties of each of the three components.
[0059] It is preferable that the polymer (1) contains, with respect to the total units, 90 to 98 mol% of TFE units, 1.5 to 9.97 mol% of PAVE units, and 0.01 to 3 mol% of units based on monomers having polar functional groups.
[0060] In addition, the monomer having polar functional groups is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic acid anhydride (alias: hymic anhydride; hereinafter also referred to as "NAH").
[0061] Specific examples of polymers (1) include the polymer described in International Publication No. 2018 / 16644.
[0062] The polymer (2) is composed only of TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol% of TFE units and 2.0 to 5.0 mol% of PAVE units with respect to the total units.
[0063] The content of PAVE units in the polymer (2) is preferably 2.1 mol% or more with respect to the total unit, and more preferably 2.2 mol% or more.
[0064] In addition, the fact that the polymer (2) does not have polar functional groups is that the number of carbon atoms constituting the polymer main chain is 1 × 10 6 This means that the number of polar functional groups in the polymer is less than 500. The number of polar functional groups is preferably 100 or less, and more preferably less than 50. The lower limit of the number of polar functional groups is typically 0.
[0065] The polymer (2) may be prepared using a polymerization initiator or a chain transfer agent that does not produce a polar functional group as a terminal group of the polymer chain, or by fluorination of an F polymer having a polar functional group (such as an F polymer having a polar functional group derived from the polymerization initiator at the terminal of the main chain of the polymer). As a method of fluorination treatment, a method using fluorine gas may be used (see Japanese Patent Publication No. 2019-194314, etc.).
[0066] The Mohs hardness of the anisotropic filler in the present invention is 4 or less, and preferably 3 or less. The Mohs hardness of the anisotropic filler is preferably 1 or more, and more preferably 2 or more. Even if the anisotropic filler is soft with a Mohs hardness in this range, due to the affinity between the anisotropic filler and the F powder, the dispersion has excellent dispersion stability, and the physical properties of the filler in the molded article are likely to be improved.
[0067] One type of anisotropic filler may be used, or two or more types with different average particle sizes or types may be used.
[0068] The shape of the anisotropic filler in the present invention may be granular, needle-shaped (fibrous), or plate-shaped. Specific shapes of the anisotropic filler include spherical, scale-shaped, lamellar, leaf-shaped, apricot-shaped, columnar, arboreal, isometric, leaf-shaped, mica-shaped, block-shaped, flat, wedge-shaped, rosette-shaped, network-shaped, and prismatic shapes.
[0069] The shape of the anisotropic filler is preferably flaky or plate-like. When using flaky or plate-like anisotropic fillers, they form a cardhouse structure, which not only makes it easy to improve the liquid properties of the dispersion (viscosity, dispersion stability, etc.) but also makes it easy to improve the orientation of the filler within the molded product, thereby making it easy to enhance its functions (mechanical strength, thermal conductivity, electrical properties, etc.).
[0070] Examples of anisotropic fillers include carbon fillers, nitride fillers, mica fillers, clay fillers, and talc fillers; fillers containing boron nitride or talc are preferred, and fillers containing boron nitride are more preferred. The crystal form of boron nitride may be hexagonal, rhombohedral, cubic, or wurtzite. The dispersion containing such anisotropic fillers exhibits excellent dispersion stability and handling properties. Furthermore, the electrical interference imparted by the filler to the F polymer within the molded article is likely to increase, and as a result, the electrical properties of the molded article (particularly dielectric loss tangent) are likely to be improved. In addition, the thermal conductivity of the molded article is likely to be improved.
[0071] In a filler containing boron nitride, the boron nitride content is preferably 95 mass% or more, more preferably 99 mass% or more, and even more preferably 99.5 mass% or more. The upper limit of the content is 100 mass%. In this case, the molded article is likely to have excellent low linear expansion and electrical properties.
[0072] When an anisotropic filler is added to water, the pH of the water may be acidic, neutral, or alkaline, and it is preferable for it to be alkaline.
[0073] The specific surface area of the anisotropic filler is preferably 1 to 20 m² / g, and more preferably 3 to 8 m² / g. In this case, the anisotropic filler becomes more easily wetted in the dispersion, and the affinity with the F powder is easily enhanced. Furthermore, in the molded article, the anisotropic filler and the F polymer are more uniformly dispersed (distributed), making it easier for the physical properties of both to be expressed in good balance.
[0074] The surface of the anisotropic filler may be surface-treated.
[0075] Examples of surface treatment agents include polyhydric alcohols (trimethylolethane, pentaerythritol, propylene glycol, etc.), saturated fatty acids (stearic acid, lauric acid, etc.), their esters, alkanolamines, amines (trimethylamine, triethylamine, etc.), paraffin waxes, silane coupling agents, silicones, polysiloxanes, and inorganic materials (oxides, hydroxides, hydrated oxides, or phosphates of aluminum, silicon, zirconium, tin, titanium, antimony, etc.).
[0076] As a surface treatment agent, a silane coupling agent is preferred. In this case, the anisotropic filler and the powder of the F polymer become more affineable, making it easier to improve the dispersion stability of the dispersion. The silane coupling agent preferably has an amino group, a thiol group, a vinyl group, an acroyloxy group, or a methacryloyloxy group.
[0077] The anisotropic filler may be an anisotropic filler having a hydrophobic part and a hydrophilic part. Examples of such anisotropic fillers include an anisotropic filler having a hydrophobic layer on the surface and a hydrophilic layer inside. Specific examples include a plate-shaped multilayer filler having a hydrophobic layer, a hydrophilic layer (water layer), and a hydrophobic layer in that order. The water content of the hydrophilic layer is preferably 0.3 mass% or more. In this case, not only is the dispersion state of the anisotropic filler in the dispersion easy to stabilize, but the orientation of the anisotropic filler is also further enhanced when molding a molded article from the dispersion, making it easy to obtain a molded article that highly combines the properties of the F polymer and the properties of the anisotropic filler.
[0078] The D50 of the anisotropic filler is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more. The D50 of the anisotropic filler is preferably 25 μm or less, and more preferably 20 μm or less. The D90 of the anisotropic filler is preferably 10 μm or more, and more preferably 15 μm or more. The D90 of the anisotropic filler is preferably 30 μm or less, and more preferably 20 μm or less. When the D50 and D90 of the anisotropic filler are within these ranges, the affinity with F powder is further improved, making it easier to further improve the dispersion stability of the dispersion and the physical properties of the molded article. Specific examples of such anisotropic fillers include flake-shaped boron nitride fillers and plate-shaped talc fillers.
[0079] The aspect ratio of the anisotropic filler is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, and particularly preferably 10 or more. The aspect ratio of the anisotropic filler is preferably 10,000 or less. In this case, it is easier to further improve the orientation of the filler within the molded article and to enhance its functionality. Specifically, not only is the dispersion state of the anisotropic filler in the dispersion easier to stabilize, but the orientation of the anisotropic filler is also further enhanced when molding the article from the dispersion, making it easier to obtain a molded article that highly combines the physical properties of the F polymer and the physical properties of the anisotropic filler.
[0080] In addition, the aspect ratio of the anisotropic filler is a value obtained by dividing the average particle size (D50) of the anisotropic filler by the average short diameter (average length in the width direction) of the anisotropic filler.
[0081] Specific embodiments of such anisotropic fillers include fillers having an average short diameter of 1 μm or less, or an average long diameter (average of the length in the longitudinal direction) of 1 μm or more. Specific examples of such anisotropic fillers include flat talc fillers.
[0082] Anisotropic fillers may have a single-layer structure or a multi-layer structure. An example of such anisotropic fillers is a three-layer talc filler.
[0083] Preferred specific examples of anisotropic fillers include boron nitride fillers (the “UHP” series manufactured by Showa Denko, the “HGP” series and “GP” series manufactured by Denka, etc.) and talc fillers (the “SG” series manufactured by Japan Talc, etc.).
[0084] In this dispersion, the D50 of the F powder is smaller than the D50 of the anisotropic filler. In short, by densely incorporating fine F powder into this dispersion, the affinity between the F powder and the anisotropic filler is increased, thereby improving the dispersion stability of this dispersion. Furthermore, in the molded article, the anisotropic filler is dispersed more uniformly, making it easier for its physical properties to be significantly expressed.
[0085] Specifically, it is preferable that the D50 of the F powder is 0.1 μm or more and less than 5 μm, and the D50 of the anisotropic filler is 1 μm or more and less than 25 μm.
[0086] A preferred embodiment of the filler included in the dispersion may be one that includes an anisotropic filler (hereinafter also referred to as "anisotropic filler 1") and also includes an inorganic filler (hereinafter also referred to as "different filler") having an average particle size smaller than that of the anisotropic filler 1. In this case, the improvement in dispersion stability of the dispersion due to the interaction between the fillers and the ability to form a dense molded article due to the different filler are balanced, making it easier to further improve the general physical properties (water resistance, low linear expansion, electrical properties, etc.) of the resulting molded article. Additionally, the different filler may be an inorganic filler having an average particle size smaller than that of the anisotropic filler 1, and its material may be the same as or different from that of the anisotropic filler 1.
[0087] In this preferred embodiment, it is preferable that the average particle size of the anisotropic filler 1 is greater than 6 μm and less than or equal to 15 μm, and also that the average particle size of the different filler is greater than or equal to 1 μm and less than or equal to 6 μm. At this time, it is preferable that the anisotropic filler 1 is a filler containing boron nitride, and also that the different filler is a filler containing boron nitride or a magnesium metasilicate filler (steatite filler). Furthermore, it is preferable that the aspect ratio of the anisotropic filler 1 is 10 or more, and also that the aspect ratio of the different filler is 40 or less, and more preferable that it is less than 10.
[0088] In this case, in the resulting molded article, the random orientation of anisotropic filler 1 is promoted by different fillers, making it easy to balance the filler properties and the molded article properties (adhesion, stiffness, etc.).
[0089] In this preferred embodiment, the average particle size of the anisotropic filler 1 is greater than 1 μm and less than or equal to 15 μm, and it is also preferable that the average particle size of the different filler is greater than or equal to 0.01 μm and less than or equal to 1 μm. In this case, it is preferable that the anisotropic filler 1 is a filler containing boron nitride, and the different filler is a filler containing silicon oxide.
[0090] The silicon oxide-containing filler is preferably a silica filler or a magnesium metasilicate filler (steatite filler). Additionally, the surface of the silicon oxide-containing filler is preferably surface-treated with a silane coupling agent.
[0091] It is preferable that the silicon dioxide-containing filler be approximately spherical. In this case, it is easy to form a dense molded product. In addition, being approximately spherical means that when observed by a scanning electron microscope (SEM), the proportion of spherical particles having a ratio of the minor axis to the major axis of 0.7 or greater is 95% or greater.
[0092] Specific examples of such silicon oxide-containing fillers include approximately spherical silica fillers (such as the "Adma Fine" series manufactured by Admatex), spherical fused silica (such as the "SFP" series manufactured by Denka), hollow silica fillers (such as the "E-SPHERES" series manufactured by Taiyō Cement, the "Silinax" series manufactured by Nittetsu Mining, the "Eco-Cospoir" series manufactured by Emerson & Calming), and steatite fillers (such as the "BST" series manufactured by Nippon Talc).
[0093] In this preferred embodiment, the random orientation of anisotropic filler 1 in the molded article is promoted by different fillers, making it easy to balance the physical properties of the filler and the physical properties of the molded article (adhesion, surface smoothness, stiffness, etc.). In short, the orientation of anisotropic filler 1 in the molded article is partially disrupted, and the electrical properties and low linear expansion attributable to the high degree of filler orientation, as well as the stiffness, adhesion, and surface smoothness attributable to the disruption of filler orientation, are easily provided in the molded article.
[0094] In addition, the filler in this preferred embodiment may be included in a state having a multi-peaked particle size distribution. In this case, from the perspective of facilitating the formation of a dense molded article, it is preferable that the peak attributable to the filler 1 among the peaks in the particle size distribution is the highest. Specifically, it is preferable that the filler be included in a state having a bi-peaked particle size distribution having peaks in a region of 6 μm or less and a region of 6 μm or more, respectively.
[0095] In addition, in this preferred embodiment, the filler may be included with at least a portion attached to the surface of the F powder, or at least a portion of the F powder may be included with the surface attached. In this case, the dispersion may be said to include a composite body of the F powder and the anisotropic filler 1, and its dispersion stability is further improved, making it easier for the general physical properties (water resistance, low linear expansion, electrical properties, etc.) of the molded article formed therefrom to be further improved.
[0096] In addition, in this preferred embodiment, the mass ratio of the content of different fillers to the content of anisotropic filler 1 is preferably 0.1 or higher, and more preferably 0.2 or higher. Furthermore, the mass ratio is preferably 2 or lower, and more preferably 1 or lower. In this case, the dispersion stability of the dispersion and the physical properties of the molded article are easily balanced.
[0097] The content of the anisotropic filler in the dispersion is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 25 mass% or more. The content of the F powder is preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 30 mass% or less.
[0098] In the dispersion, it is preferable that the content of the F polymer and the content of the anisotropic filler are each 5 mass% or more. It is preferable that the sum of the contents of both is 60 mass% or less. Even when the F polymer and the anisotropic filler are each contained at such high proportions (contents), the dispersion exhibits excellent dispersion stability as described above, and it is easy to form a molded article that highly possesses the physical properties of both.
[0099] It is desirable that this dispersion additionally include a surfactant to improve dispersion stability and handling properties.
[0100] It is preferable that the surfactant be nonionic.
[0101] It is preferable that the hydrophilic portion of the surfactant has an oxyalkylene group or an alcoholic hydroxyl group.
[0102] The oxyalkylene group may consist of one type or two or more types. In the latter case, different types of oxyalkylene groups may be arranged randomly or in blocks.
[0103] The oxyalkylene group is preferably an oxyethylene group.
[0104] It is preferable that a small portion of the surfactant has an acetylene group, a polysiloxane group, a perfluoroalkyl group, or a perfluoroalkenyl group. In other words, the surfactant is preferably an acetylene-based surfactant, a silicone-based surfactant, or a fluorine-based surfactant, and a silicone-based surfactant is more preferable.
[0105] As for fluorinated surfactants, fluorinated surfactants having a hydroxyl group (particularly an alcoholic hydroxyl group) or an oxyalkylene group and a perfluoroalkyl group or a perfluoroalkenyl group are more preferred.
[0106] Specific examples of surfactants include the "Ptergent" series (manufactured by Neos Co.), the "Surflon" series (manufactured by AGC Seimi Chemical Co.), the "Megapac" series (manufactured by DIC Co.), the "Unidine" series (manufactured by Daikin Industries Co.), "BYK-347," "BYK-349," "BYK-378," "BYK-3450," "BYK-3451," "BYK-3455," "BYK-3456" (manufactured by Big Chem Japan Co., Ltd.), "KF-6011," and "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0107] The content of the surfactant in the dispersion is preferably 1 to 15 mass%. In this case, the affinity between the components is enhanced, making it easier to further improve the dispersion stability of the dispersion.
[0108] The liquid dispersion medium in the present invention is a liquid compound that is inert at 25°C and functions as a dispersion medium for F powder and anisotropic filler. The liquid dispersion medium may be water or a non-aqueous dispersion medium. The liquid dispersion medium may be one type or two or more types. In this case, it is preferable to use different types of liquid compounds.
[0109] The boiling point of the liquid dispersion medium is preferably 125 to 250°C. In this case, when forming a molded article from this dispersion, the anisotropic filler is easily oriented, and the physical properties of the molded article are easily improved.
[0110] As for the liquid dispersion medium, one or more liquid compounds selected from the group consisting of amides, ketones, and esters are preferred from the perspective of dispersion stability of the dispersion, and N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone, or cyclopentanone are more preferred.
[0111] The content of the liquid dispersion medium in the dispersion is preferably 50 mass% or more, and more preferably 60 mass% or more. The content of the liquid dispersion medium is preferably 90 mass% or less, and more preferably 80 mass% or less.
[0112] The viscosity of the dispersion is preferably 50 mPa·s or higher, and more preferably 100 mPa·s or higher. The viscosity of the dispersion is preferably 10,000 mPa·s or lower, more preferably 1,000 mPa·s or lower, and even more preferably 800 mPa·s or lower.
[0113] The tick consumption ratio of the dispersion is preferably 1.0 or higher. The tick consumption ratio of the dispersion is preferably 3.0 or lower, and more preferably 2.0 or lower.
[0114] The component dispersion layer ratio of the dispersion is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. Here, the component dispersion layer ratio is a value calculated by the following formula from the total height of the dispersion inside the screw tube and the height of the component dispersion layer before and after standing, when the dispersion (18 mL) is placed in a screw tube (inner volume: 30 mL) and left to stand at 25°C for 14 days.
[0115] Component dispersion layer ratio (%) = (Height of component dispersion layer) / (Total height of the dispersion) × 100
[0116] In addition, if no component dispersion layer is confirmed after settling and there is no change in state, the total height of the dispersion solution is considered to be unchanged, and the component dispersion layer ratio is set to 100%.
[0117] This dispersion has excellent handling properties, as it is easy to adjust the viscosity, thixotropy, or component dispersion ratio within this range through the mechanism of action described above.
[0118] This dispersion may additionally contain other resins (polymers) different from the F polymer. The other resins may be thermosetting resins or thermoplastic resins.
[0119] Other resins include epoxy resin, maleimide resin, urethane resin, elastomer, polyimide, polyamic acid, polyamideimide, polyphenylene ether, polyphenylene oxide, liquid crystal polyester, and fluoropolymers other than F polymer.
[0120] Another preferred embodiment of the resin is an aromatic polymer varnish. The aromatic polymer is preferably an aromatic polyimide or an aromatic polyamic acid, and a thermoplastic aromatic polyimide is more preferred. In this case, the physical properties of the F polymer and the anisotropic filler are easily expressed in the molded article. Furthermore, when forming a molded article from this dispersion, the shedding of the F powder is suppressed, and the adhesion is also easily improved.
[0121] The content of the aromatic polymer in the dispersion is preferably 1 to 30 mass%, and more preferably 5 to 25 mass%. The ratio of the mass of the aromatic polymer content to the content of the F polymer is preferably 1.0 or less, and more preferably 0.1 to 0.7.
[0122] Another preferred embodiment of the resin is polytetrafluoroethylene (PTFE) powder. In this case, physical properties based on PTFE (electrical properties such as low dielectric loss tangent) are easily exhibited in the molded article. Additionally, PTFE acts as a nucleating agent, making it easier for the F polymer in the molded article to form microcrystals; this improves adhesion to the surface of the molded article and increases its adhesive properties. Furthermore, it is easy to improve the orientation of the filler within the molded article, thereby enhancing its functionality.
[0123] PTFE is preferably PTFE (low molecular weight PTFE) having a number average molecular weight (Mn) of 200,000 or less calculated based on the following formula (1).
[0124] Mn = 2.1 × 10 10 × ΔHc -5.16 ··· (1)
[0125] In Equation (1), ΔHc represents the crystallization heat (cal / g) of PTFE measured by differential scanning calorimetry.
[0126] The Mn of low molecular weight PTFE is preferably 100,000 or less, and more preferably 50,000 or less. The Mn of low molecular weight PTFE is preferably 10,000 or more.
[0127] The PTFE content in the dispersion is preferably 1 to 30 mass%, and more preferably 5 to 20 mass%. The ratio of the mass of PTFE content to the mass of F polymer content is preferably 1.0 or less, and more preferably 0.1 to 0.4.
[0128] In the case where other resins are included, the dispersion may be prepared by mixing the dispersion with powder of other resins, or by mixing the dispersion with a varnish containing other resins.
[0129] In addition to the components described above, this dispersion may also contain additives such as thixotropic agents, defoaming agents, silane coupling agents, dehydrating agents, plasticizers, weathering agents, antioxidants, heat stabilizers, lubricants, antistatic agents, whitening agents, coloring agents, conductive agents, release agents, surface treatment agents, viscosity modifiers, flame retardants, and isotropic fillers.
[0130] The dispersion can be prepared by mixing F powder, an anisotropic filler, and a liquid dispersion medium, and it is preferable to prepare a liquid composition containing F powder and a liquid composition containing anisotropic filler by separately preparing them and mixing the two.
[0131] A specific method for manufacturing the dispersion may be a method of mixing F powder, anisotropic filler 1, a different filler, and a liquid dispersion medium. When mixing, the F powder and the liquid dispersion medium may be mixed in advance to form a liquid composition, or the anisotropic filler 1 and the different filler may be mixed in advance.
[0132] Mixers used for mixing include mixers with stirring blades, Henschel mixers, ribbon blenders, oscillating mixers, vibrating mixers, rotary mixers, and specifically, homodispersers, homogenizers, and ball mills.
[0133] The mixing method may be either batch or continuous. For batch mixing, a Henschel mixer, a pressure kneader, a Banbury mixer, or a planetary mixer is preferred.
[0134] Mixing is preferably carried out by stirring, and more preferably by rotary stirring with stirring blades.
[0135] The stirring speed is preferably 800 rpm or higher, and more preferably 2000 rpm or higher. The stirring speed is preferably 10000 rpm or lower, and more preferably 8000 rpm or lower. In this case, shear is applied to the F powder and the anisotropic filler, making it easy to break down aggregates and easy to obtain the dispersion with excellent dispersibility.
[0136] In addition, if the anisotropic filler is in the form of flakes or plates, the layered aggregates (secondary particles) of the anisotropic filler are typically efficiently broken down to form a card house structure, making it easy to form the dispersion with excellent dispersibility.
[0137] The molded article of the present invention (hereinafter also referred to as "the present molded article") comprises a tetrafluoroethylene-based polymer containing PAVE units (hereinafter also referred to as "PFA-based polymer") and an anisotropic filler having a Mohs hardness of 4 or less. The PFA-based polymer is a polymer having polar functional groups, or a polymer containing 2.0 to 5.0 mol% of PAVE units relative to the total units and not having polar functional groups, and the proportion (content) of the anisotropic filler in the present molded article is 10 mass% or more.
[0138] Examples of the shapes of the molded article include lamellar, plate-like, and bulk forms, and a lamellar shape is preferred. The thickness of the lamellar molded article is preferably 150 μm or less. Such a lamellar molded article is useful for manufacturing impregnated articles such as films and prepregs, or laminated boards.
[0139] The definition and scope of the anisotropic filler in the present molded article are the same as those of the anisotropic filler in the present dispersion, including preferred embodiments.
[0140] In the molded article, the type and range of polar functional groups of the PFA-based polymer are the same as those of the F polymer, including preferred embodiments. Additionally, the PFA-based polymer is preferably polymer (1) or polymer (2).
[0141] The content of the anisotropic filler in the molded article is preferably 15 mass% or more, and more preferably 25 mass% or more. The content of the anisotropic filler is preferably 50 mass% or less, and more preferably 40 mass% or less.
[0142] The content of the PFA-based polymer in the molded article is preferably 40 mass% or more, more preferably 50 mass% or more, and even more preferably 60 mass% or more. The content of the PFA-based polymer is preferably 95 mass% or less, more preferably 80 mass% or less, and even more preferably 70 mass% or less. When the content of the PFA-based polymer is within this range, the physical properties of the PFA-based polymer are easily expressed significantly in the molded article. In addition, the shedding of anisotropic filler powder from the molded article is suppressed.
[0143] The molded article preferably further comprises an aromatic polymer (particularly an aromatic polyimide) or PTFE. The respective definitions and ranges of the aromatic polymer and PTFE in the molded article, and the ratio of the mass of each content to the content of the F polymer, are the same as those in the dispersion.
[0144] It is preferable that the present molded article be formed from the present dispersion. Specifically, by applying the present dispersion to the surface of a substrate and removing the liquid dispersion medium, a layer (hereinafter also referred to as "the present layer") comprising a PFA-based polymer and an anisotropic filler can be easily formed on the surface of the substrate as the present molded article. More specifically, by applying the present dispersion to the surface of a substrate, heating the substrate to remove the liquid dispersion medium, and further heating to melt and sinter the PFA-based polymer, a laminate having a substrate and the present layer formed on the surface of the substrate is obtained. The temperature for the former heating is preferably 120°C to 200°C. Meanwhile, the temperature for the latter heating is preferably 250°C to 400°C, and more preferably 300°C to 380°C.
[0145] Examples of substrates include metal substrates (metal foils such as copper, nickel, aluminum, titanium, their alloys, etc.), resin films (films such as polyimide, polyarylate, polysulfone, polyallylsulfone, polyamide, polyetheramide, polyphenylene sulfide, polyallyletherketone, polyamideimide, liquid crystal polyester, liquid crystal polyesteramide, etc.), and prepregs (precursors of fiber-reinforced resin substrates).
[0146] It is preferable to apply the dispersion by coating. Examples of coating methods include spray method, roll coating method, spin coating method, gravure coating method, micro-gravure coating method, gravure offset method, knife coating method, kiss coating method, bar coating method, die coating method, Fountain Mayer bar method, and slot die coating method.
[0147] Each heating method includes using an oven, using a ventilation drying oven, and irradiating with heat rays such as infrared rays.
[0148] The thickness of the present layer is preferably 0.1 to 150 μm. Specifically, if the substrate is a metal foil, the thickness of the present layer is preferably 1 to 30 μm. If the substrate is a resin film, the thickness of the present layer is preferably 1 to 150 μm, and more preferably 10 to 50 μm.
[0149] The dispersion may be applied to only one surface of the substrate or to both surfaces of the substrate. In the former case, a laminate having the layer on one surface of the substrate is obtained, and in the latter case, a laminate having the layer on both surfaces of the substrate is obtained. Since the latter laminate is less prone to warping, it has excellent handling properties during processing.
[0150] Specific examples of such laminates include a metal foil and a metal-coated laminate having the present layer on at least one surface of the metal foil, and a polyimide film and a multilayer film having the present layer on both surfaces of the polyimide film.
[0151] These laminates have excellent general physical properties, such as electrical properties, and are therefore desirable as printed circuit board materials. Specifically, these laminates can be used to manufacture flexible printed circuit boards or rigid printed circuit boards.
[0152] Examples
[0153] The present invention will be described in detail below by way of examples, but the present invention is not limited thereto.
[0154] 1. Preparation of each component
[0155] [Powder]
[0156] Powder 1: Contains TFE units, NAH units, and PPVE units in this order at 97.9 mol%, 0.1 mol%, and 2.0 mol%, respectively, and carbonyl groups with a carbon number of 1 × 10⁶ in the main chain. 6 Powder (D50: 2.1 μm) consisting of PFA-based polymer 1 (melting temperature: 300 ℃) having 1000 particles per unit
[0157] Powder 2: Contains 97.5 mol% and 2.5 mol% of TFE units and PPVE units in this order, and carbonyl groups with a main chain having 1 × 10 carbon atoms. 6 Powder (D50: 1.8 μm) composed of PFA-based polymer 2 (melting temperature 305 ℃) having 40 cells per cell
[0158] Powder 3: Powder composed of PFA-based polymer 2 (D50: 5.3 μm)
[0159] Powder 4: Powder composed of PTFE with a number average molecular weight of 20,000 (D50: 3.2 µm)
[0160] [Anisotropic Filler]
[0161] Filler 1: Flake-like filler composed of boron nitride (D50: 7.0 μm)
[0162] Filler 2: Flake-like filler composed of boron nitride (D50: 3.7 μm)
[0163] Filler 3: Flake-like filler composed of boron nitride (D50: 7.3 μm)
[0164] Filler 4: Plate-shaped talc filler with a 3-layer structure having hydrophobic, hydrophilic, and hydrophobic layers in that order (D50: 4.5 μm, average major axis: 5.1 μm, average minor axis: 0.2 μm, aspect ratio: 25, manufactured by Japan Talc Co., Ltd. "SG-95")
[0165] In addition, the Mohs hardness of fillers 1 to 3 is 2, and the Mohs hardness of filler 4 is 1. Fillers 1, 2, and 4 are surface-treated with a silane coupling agent.
[0166] [Liquid dispersion medium]
[0167] NMP: N-methyl-2-pyrrolidone
[0168] [Surfactant]
[0169] Surfactant 1 : CH2= C(CH3)C(O)OCH2CH2(CF2)6F and CH2= C(CH3)C(O)(OCH2CH2) 23 A nonionic polymer that is an OH copolymer and has a fluorine content of 35 mass%
[0170] [Aromatic Polymer Varnish]
[0171] Varnish 1: Varnish in which thermoplastic aromatic polyimide (PI1) is dissolved in NMP (solids concentration: 18 mass%)
[0172] 2. Example of preparation of dispersion
[0173] (Example 1)
[0174] First, Powder 1, Varnish 1, Surfactant 1, and NMP were added to a pot, and zirconia balls were added. Then, the pot was rolled at 150 rpm for 1 hour to prepare the composition. In another pot, Filler 1, Surfactant 1, and NMP were added, and zirconia balls were added. Then, the pot was rolled at 150 rpm for 1 hour to prepare the composition.
[0175] In another port, the composition of both was introduced, and zirconia balls were introduced. Then, the port was rolled at 150 rpm for 1 hour to obtain dispersion 1 (viscosity: 400 mPa·s) containing powder 1 (11 parts by mass), filler 1 (11 parts by mass), PI1 (7 parts by mass), surfactant 1 (4 parts by mass) and NMP (67 parts by mass).
[0176] (Examples 2–9)
[0177] Dispersions 2 to 9 were obtained in the same manner as Example 1, except that the types and amounts of powder, filler, varnish, surfactant, and liquid dispersion medium were changed as shown in Table 1 below.
[0178] (Example 10)
[0179] A dispersion 10 was obtained in the same manner as in Example 1, except that 3 parts by mass of filler 1 and 8 parts by mass of filler 2 were used instead of 11 parts by mass of filler 1.
[0180]
[0181] 3. Example of manufacturing a molded article
[0182] A wet film was formed by applying dispersion 1 to the surface of a long copper foil (thickness 18 μm) using a bar coater. Subsequently, the metal foil with the formed wet film was passed through a drying oven at 120 °C for 5 minutes and dried by heating to obtain a dry film. Afterward, the dry film was heated in a nitrogen oven at 380 °C for 3 minutes. Thus, a laminate 1 was manufactured having a metal foil and a polymer layer (thickness 5 μm) as a molded product comprising a molten sintered product of powder 1 and filler 1 on its surface.
[0183] Laminates 2 to 10 were each manufactured in the same manner as laminate 1, except that dispersion 1 was changed to dispersions 2 to 10 respectively.
[0184] 4. Evaluation
[0185] 4-1. Dispersion Stability of Dispersions
[0186] After storing dispersions 1 to 10 in a container at 25°C, their dispersibility was visually checked, and dispersion stability was evaluated according to the following criteria.
[0187] [metewand]
[0188] ◎ : No aggregates are visible.
[0189] ○ : Fine aggregates were observed adhering to the side walls of the container. They were uniformly redispersed upon light stirring.
[0190] △ : It is visible that aggregates have settled at the bottom of the container. When shearing is applied and stirring is performed, they are uniformly redispersed.
[0191] × : It is observed that aggregates have settled at the bottom of the container. Redispersion is difficult even when stirring with shear.
[0192] 4-2. Physical Properties of Laminates
[0193] 4-2-1. Surface Smoothness
[0194] For the polymer layers of laminates 1 to 9, the surface smoothness was visually inspected, and the surface smoothness was evaluated according to the following criteria.
[0195] [metewand]
[0196] ○ : The entire surface of the polymer layer is smooth.
[0197] △ : Unevenness caused by the absence of polymer or filler is visible at the edge of the surface of the polymer layer.
[0198] × : Irregularities caused by the absence of polymer or inorganic fillers are visible across the entire surface of the polymer layer.
[0199] 4-2-2. Coefficient of Linear Expansion
[0200] For each of laminates 1 to 4, 9 and 10, a square test specimen of 180 mm in width and length was cut out, and the coefficient of linear expansion of the test specimen in the range of 25 ℃ to 260 ℃ was measured according to the measurement method specified in JIS C 6471:1995.
[0201] [metewand]
[0202] ○ : 30 ppm / ℃ or less.
[0203] × : Exceeds 30 ppm / ℃.
[0204] 4-2-3. Genetic Loss Traction
[0205] For each of laminates 1 to 4, 9 and 10, a single polymer layer was fabricated by removing the copper foil of the laminate by etching with an aqueous ferric chloride solution, and the dielectric loss tangent (measurement frequency: 10 GHz) of the polymer layer was measured using the SPDR (Split Post Dielectric Resonance) method.
[0206] [metewand]
[0207] ○ : The genetic apex is less than 0.0010.
[0208] △ : The genetic null tangent is 0.0010 or greater and 0.0025 or less.
[0209] × : The genetic tangent is greater than 0.0025.
[0210] The results of each evaluation are summarized in Table 2 below.
[0211]
[0212] 5. Example of preparation of dispersion (The 2)
[0213] (Example 11)
[0214] First, Powder 1, Surfactant 1, and NMP were added to a pot and mixed, and the composition was adjusted by stirring with a homodisper at 2000 rpm for 1 hour. Filler 1, Surfactant 1, and NMP were added to another pot and the composition was adjusted by stirring with a homodisper at 2000 rpm for 1 hour. Both compositions were added to yet another pot and stirred with a homodisper at 2000 rpm for 1 hour to obtain a dispersion 11 (viscosity: 300 mPa·s, component dispersion ratio: 80%) containing Powder 1 (11 parts by mass), Filler 1 (11 parts by mass), Surfactant 1 (4 parts by mass), and NMP (74 parts by mass).
[0215] (Example 12)
[0216] A dispersion 12 was obtained in the same manner as in Example 11, except that an ultrasonic homogenizer that does not involve stirring by stirring blades was used instead of a homodisper (viscosity: 300 mPa·s, component dispersion layer ratio: 50%).
[0217] 6. Example of manufacturing a laminate (The 2)
[0218] A liquid film was formed on the surface of an aluminum foil with a thickness of 18 μm by rolling-to-roll coating with a dispersion 11 using a gravure reverse method. Subsequently, the aluminum foil with the liquid film formed thereon was passed through a drying oven at 120°C for 5 minutes and dried by heating. Afterward, the dried film was heated at 340°C for 3 minutes in a far-infrared oven under a nitrogen atmosphere. In this way, a laminate 11 was manufactured in which a polymer layer (thickness: 10 μm) was formed on the surface of the aluminum foil. Additionally, a laminate 12 was manufactured in the same manner as laminate 11, except that dispersion 12 was used instead of dispersion 11.
[0219] As a result of observing the cross-sections of each laminate using SEM, the distribution of filler 1 in the polymer layer of laminate 11 was denser than in the polymer layer of laminate 12. In addition, the dielectric loss tangent of the polymer layer of laminate 11 was lower than that of laminate 12. Laminate 11 had superior thermal conductivity and bendability compared to laminate 12.
[0220] Industrial applicability
[0221] The dispersion of the present invention has excellent dispersion stability and can be used to manufacture molded articles (films, prepregs, laminates, coatings, etc.) that have physical properties based on F polymers (PFA-based polymers) and characteristics based on anisotropic fillers. The molded article of the present invention is useful as an antenna component, printed circuit board, aircraft component, automobile component, sports equipment, food industry product, paint, cosmetic, etc. Specifically, it is useful as a heat dissipation member, wire sheathing material (aircraft wire, etc.), electrical insulating tape, oil drilling insulating tape, material for printed circuit board, separator (precision filter membrane, ultrafiltration membrane, reverse osmosis membrane, ion exchange membrane, dialysis membrane, gas separation membrane, etc.), electrode binder (for lithium secondary batteries, fuel cells, etc.), copy roll, cover for furniture, automobile dash boat, home appliance, etc., sliding member (load bearing, sliding shaft, valve, bearing, gear, cam, belt conveyor, food conveying belt, etc.), tool (shovel, file, awl, saw, etc.), boiler, hopper, pipe, oven, grilling mold, chute, die, toilet, container covering material, and outer surface covering material for heat exchangers (fin, heat transfer tube, etc.) of refrigeration equipment, etc.
Claims
Claim 1 A dispersion comprising a powder of a tetrafluoroethylene-based polymer containing a unit based on perfluoro(alkyl vinyl ether) or a unit based on hexafluoropropylene, an anisotropic filler having a Mohs hardness of 4 or less, and a liquid dispersion medium, wherein the average particle size of the powder is smaller than the average particle size of the anisotropic filler, wherein the anisotropic filler comprises boron nitride or talc, the average particle size of the powder is 0.01 μm or more and 10 μm or less, the average particle size of the anisotropic filler is 1 μm or more and 25 μm or less, the content of the anisotropic filler is 10 mass% or more, the sum of the contents of the tetrafluoroethylene-based polymer and the anisotropic filler is 60 mass% or less, and the shape of the anisotropic filler is flake-like or plate-like. Claim 2 A dispersion according to claim 1, wherein the content of the tetrafluoroethylene-based polymer is 5 mass% or more. Claim 3 A dispersion according to claim 1, wherein the aspect ratio of the anisotropic filler is 2 or more. Claim 4 In claim 1, a dispersion comprising additionally polytetrafluoroethylene powder or an aromatic polymer. Claim 5 A dispersion according to claim 1, wherein the component dispersion layer ratio is 60% or more. Claim 6 A method for preparing a dispersion described in any one of claims 1 to 5, comprising mixing the powder, the anisotropic filler, an inorganic filler having an average particle size smaller than that of the anisotropic filler, and a liquid dispersion medium. Claim 7 A manufacturing method according to claim 6, wherein the above mixing is carried out by stirring. Claim 8 A molded article comprising a tetrafluoroethylene-based polymer containing a perfluoro(alkyl vinyl ether)-based unit and an anisotropic filler having a Mohs hardness of 4 or less, wherein the tetrafluoroethylene-based polymer is a polymer having polar functional groups, or a polymer that does not have polar functional groups and contains 2.0 to 5.0 mol% of the perfluoro(alkyl vinyl ether)-based unit relative to the total unit, the proportion of the anisotropic filler in the molded article is 10 mass% or more, the anisotropic filler contains boron nitride or talc, the average particle size of the anisotropic filler is 1 μm or more and 25 μm or less, and the shape of the anisotropic filler is flake-like or plate-like. Claim 9 In claim 8, a molded article in which the aspect ratio of the anisotropic filler is 2 or greater. Claim 10 A molded article according to claim 9, wherein the anisotropic filler is a flaky anisotropic filler comprising boron nitride or a plate-shaped anisotropic filler comprising talc. Claim 11 In claim 8, a molded article comprising additionally polytetrafluoroethylene or an aromatic polymer. Claim 12 A molded article according to any one of claims 8 to 11, wherein the molded article is a layered molded article with a thickness of 150 μm or less. Claim 13 delete Claim 14 delete Claim 15 delete
Citation Information
Patent Citations
Fluoropolymer filled with conductor
JP1994001902A
Atomizable powder of non-fibrillating fluoropolymer
JP2002540275A
A polymer composition with uniformly distributed nano-sized inorganic particles
KR1020130118995A
Resin powder, method for producing same, complex, molded article, method for producing ceramic molded article, metal laminated plate, print substrate, and prepreg
KR1020170039080A
